ANALISIS DAN IMPLEMENTASI SMS GATEWAY SEBAGAI AUTO-RESPON LAYANAN INFORMASI BERBASIS STORE AND FORWARD - Iwan Koerniawan; Fujiama Diapoldo Silalahi (JURNAL TEKNOLOGI INFORMASI DAN KOMUNIKASI, 2020)
Customer service is a routine work done by a business entity in the process of goods supply and sale. Effective and valid service for consumers is the dream of all companies to generate greater profits. But, the service of information to the consumers as the main link to the consumer sometimes gets the difficulty in fulfilling the demand for information from each consumer. This is due to various reasons, because the data has not been updated, not. integrated about the latest promo information, the difficulty in memorizing the existing product specifications, up-to-date price changes and complex goods ordering system. The existence of the above problems becomes the basis for researchers to conduct the research based on online web-based technology and SMS GATEWAY communication technology. System which is built will offer the solution of the information service`s problem fot the consumers and cistomers. This research is conducted in UD Usaha Makmur environment which is located at Jl MT Haryono 63 Semarang Central Java. This research discusses about how to conduct auto response information service system which is based on store and forward and its efficient and effective implementation.The purpose of this study is to build a software about information service system that apply, and its implementation is effective. While the long term purpose of this research is to built a standard information service system that can be used and achieved by the societies. The scope of this research is to discuss the correct procedure of auto response service and GATEWAY SMS implementation as media for the recipient and the sender of information for its validity review. The research method used was R & D Borg and Gall which is modified with 6 steps